Sacrifice - Kemmerer, Brigid (Kemmerer, Brigid. Elemental series., 2014)
The battle between the Elementals and their enemies comes to a head as the eldest Merrick brother struggles to save his family and the girl he loves from the Guides sent to destroy them.